Emerging trends and hotspots in metabolic dysfunction-associated fatty liver disease (MAFLD) research from 2012 to 2021: A bibliometric analysis - Liao, Yudi; Wang, Liya; Liu, Fang; Zhou, Yanyu; Lin, Xiaoqi; Zhao, Zijun; Xu, Saihong; Tang, Dan; Jiao, Yingfu; Yang, Liqun; Yu, Weifeng; Gao, Po (Frontiers in Endocrinology, 2023)
Background: Metabolic dysfunction-associated fatty liver disease (MAFLD) has become the most common chronic liver disease. MAFLD is a major risk factor for end-stage liver disease including cirrhosis and primary liver cancer. The pathogenesis of MAFLD is complex and has not yet been clarified. To the best of our knowledge, few studies have conducted quantitative bibliometric analysis to evaluate published MAFLD research. In this study, we conducted a comprehensive analysis of MAFLD publications over the past decade to summarize the current research hotspots and predict future research directions in this field. Methods: Articles into MAFLD published from 2012 to 2021 were identified from the Science Citation Index-Expanded of Web of Science Core Collection. CiteSpace software, VOSviewer, the “bibliometrix” R package, and the Online Analysis Platform of Literature Metrology were used to analyze the current publication trends and hotspots. Results: We retrieved 13959 English articles about MAFLD published from 2012 to 2021. Primary sites of publication were dominated by the United States until 2014, when China became the source of most published MAFLD-related research papers. The United States was found to be the most engaged country in international cooperative efforts. Shanghai Jiao Tong University was the most productive institution. Loomba R was the most productive author with 123 articles. The co-cited keyword cluster tag showed ten main clusters: #0 liver fibrosis, #1 hemoglobin, #2 metabolic associated fatty liver disease, #3 egcg, #4 myocardial infarction, #5 heart disease, #6 pnpla3, #7 hepatocellular carcinoma, #8 noninvasive marker, and #9 children. Keyword burst analysis showed that gut microbiota was the highest-intensity research hotspot. Conclusion: In the past decade, the number of publications on MAFLD increased dramatically, especially in the last three years. Gut microbiota became an important research direction for etiological and therapeutic investigations into MAFLD. Insulin resistance was also a key factor in studying the development of MAFLD in recent years. Liver fibrosis was an important focus of disease development. This study provides systematic information, helps guide future research, and helps to identify mechanisms and new treatment methods for MAFLD.